2016
DOI: 10.1016/j.rchipe.2015.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico etiológico en meningitis y encefalitis por técnicas de biología molecular

Abstract: The addition of PCR to conventional diagnostic methods in CNS infections increases the probability of finding the causal agent. This allows a more adequate, timely and rational management of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
5
0
3
Order By: Relevance
“… 27 Highlighting the importance of PCR assay, Smith and et al reported 2 patients with HSV‐1 meningoencephalitis. 28 After analyzing 21 patients with acute bacterial meningitis in Sweden, none of the CSF samples showed the DNA of HSV‐1, HSV‐2, VZV, EBV, and HHV‐6. 29 In patients, who did not have any blister or rash, herpesviruses (HHVs) were detected in 12 (6.9%) CSF samples (6.3% in tick‐borne encephalitis cases, 7.8% in people suffering from enteroviral meningitis and 1 (0.9%) in control group).Furthermore, total protein in HHV DNA‐positive samples was higher than HHV‐negative ones.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Highlighting the importance of PCR assay, Smith and et al reported 2 patients with HSV‐1 meningoencephalitis. 28 After analyzing 21 patients with acute bacterial meningitis in Sweden, none of the CSF samples showed the DNA of HSV‐1, HSV‐2, VZV, EBV, and HHV‐6. 29 In patients, who did not have any blister or rash, herpesviruses (HHVs) were detected in 12 (6.9%) CSF samples (6.3% in tick‐borne encephalitis cases, 7.8% in people suffering from enteroviral meningitis and 1 (0.9%) in control group).Furthermore, total protein in HHV DNA‐positive samples was higher than HHV‐negative ones.…”
Section: Discussionmentioning
confidence: 99%
“…Se realizó el diagnóstico etiológico de la MA en dos casos, uno de ellos fue citomegalovirus y el otro caso fue enterovirus; en estudios como el de Saraiva et al, se observa un mayor uso de las pruebas moleculares (32) , que permitió identificar el agente etiológico de la MA en el 29,7% de sus casos, algo similar a los estudios de Dueguer et al (36) y Conca et al (37) .…”
Section: Discussionunclassified
“…[129] eficacia de las pruebas moleculares, es necesario aprovechar esta tecnología puesto que beneficia al paciente facilitando el diagnostico etiológico, repercutiendo en la clínica y en decisiones terapéuticas; así mismo, disminuye el uso de antibióticos y días de hospitalización y genera mayores beneficios en costo-efectividad (37) .…”
Section: Discussionunclassified
“…Molecular methods have dramatically improved the ability to diagnose CNS infections in a reasonable and effective time frame. Several PCR-derived techniques have collectively expanded the flexibility and rigor of currently available laboratory diagnostic methods 48, 49 .…”
Section: Molecular Methods In Diagnosis Of Cns Infectionsmentioning
confidence: 99%
“…Several multiplex PCR assays have been developed to identify bacterial pathogens in CSF targeting the most common causes of meningitis: S. pneumoniae , N. meningitis , H. influenzae 26, 48, 76, 77 , L. monocytogenes , 26, 77 , S. agalactiae , S. aureus , E. coli 26 , and M. pneumoniae 26 . A multiplex PCR followed by Luminex suspension array can simultaneously detect eight bacterial and viral pathogens in CSF including N. meningitis , S. pueumoniae , E. coli , S. aureus , L. monocytogenes , S. agalactiae , HSV-1/2, and VZV 78 .…”
Section: Molecular Methods In Diagnosis Of Cns Infectionsmentioning
confidence: 99%